Noldeke’s Qur’anic Textual Criticism: An Analysis in German Orientalist Context - Saeed, Riaz Ahmad; Muhammad Khubaib (Journal of Islamic and Religious Studies, 2020)
It is a fact that the majority of the Orientalists consider the Holy Qur’ān as the primary source of Islamic faith, worship and teachings, so most of them have tried their best to make Qur’ān unauthentic and contradictory. For that purpose, they have directed to devote all their efforts to prove it a human-authored book. Consequently, they want to prove the Holy Prophet Muhammad (PBUH) as a fabricated Prophet. In this regard, Theodore Noldeke is a German Orientalist who has some objections to the text of the Holy Quran. In this paper, efforts are made to respond to these objections of Noldeke. Furthermore, the study analyzed the Orientalist movement in the German context. It is perceived as an eye open truth the Holy Quran is free from any human error and textual amendment but at that point, Theodore Noldeke tries to get benefit from diverse and somehow weak Tafsīr literature and Muslim scholarly difference of opinion in this regard. Moreover, German Orientalism is an important chapter of the Global Orientalists Movement but the world could able to know it later. Therefore, this study recommends that Muslim scholars must respond to the objections and reservations of German Orientalists in the proper and best way. Analytical research methodology has been adopted in this study with a qualitative approach.